Handwriting Tics in Tourette’s Syndrome: A Single Center Study - Zanaboni Dina, Carlotta; Bona, Alberto R.; Zekaj, Edvin; Servello, Domenico; Porta, Mauro (Frontiers in Psychiatry, 2016)
Tourette’s syndrome (TS) is a neurodevelopmental disorder typically defined by multiple motor tics and at least one sound tic, beginning in childhood or in adolescence. Handwriting is one of the most impaired school activities for TS patients because of the presence of tics that hamper learning processes. In this paper, we present a case of handwriting tics in a TS patient highlighting the main features.